Microtechnology-based in vitro models: Mimicking liver function and pathophysiology - Seung Yeon Lee; Donghyun Kim; Seung Hwan Lee; Jong Hwan Sung (APL Bioengineering, 2021)
The liver plays important roles in drug metabolism and homeostasis. The metabolism and biotransformation can not only affect the efficacy of drugs but also result in hepatotoxicity and drug-induced liver injury. Understanding the complex physiology of the liver and the pathogenetic mechanisms of liver diseases is essential for drug development. Conventional in vitro models have limitations in the ability to predict drug effects, due to the lack of physiological relevance. Recently, the liver-on-a-chip platform has been developed to reproduce the microarchitecture and in vivo environment of the liver. These efforts have improved the physiological relevance of the liver tissue used in the platform and have demonstrated its applicability to drug screening and disease models. In this review, we summarize the recent development of liver-on-a-chip models that closely mimic the in vivo liver environments and liver diseases.